Precision surgery and avoiding over-treatment. Issue 5 (May 2017) - Hosseini, A.; Khoury, A.L.; Esserman, L.J.
Abstract: Over-diagnosis and over-treatment are consequences of greater awareness about breast cancer, more intensive screening, and the resultant identification of more cases of breast cancer that are low or ultralow risk. This area represents an important opportunity to optimize the delivery of appropriate targeted therapy for breast cancer patients. Despite the evolution of breast cancer care over the last few decades and our ability to tailor treatment to biology, a one-size fits all approach is still prevalent in the local and regional management of and screening for breast cancer, failing to reflect the unique biology and tumor characteristics of each patient. In this review, we explore how we can use new tools to better define tumor biology and also how we can change current clinical practices based on already available data. Every surgeon should be knowledgeable about how to craft personalized breast cancer care in the areas of systemic therapy, adjuvant radiation therapy, management of ductal carcinoma in situ (DCIS), precision surgery, and breast cancer screening.